2009
DOI: 10.1243/09544119jeim663
|View full text |Cite
|
Sign up to set email alerts
|

STING: a soft-tissue intervention and neurosurgical guide to access deep brain lesions through curved trajectories

Abstract: Current trends in surgical intervention favour a minimally invasive approach, in which complex procedures are performed through very small incisions. Specifically, in neurosurgery there is a need for minimally invasive keyhole access, which conflicts with the lack of manoeuvrability of conventional rigid instruments. In an attempt to address this shortcoming, the current state of progress is reported on a soft-tissue intervention and neurosurgical guide (STING) to access deep brain lesions through curved traje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 23 publications
0
76
0
Order By: Relevance
“…For example, Oldfield et al [18] described a 6-mm diameter four-part needle prototype with reciprocally moving segments. Tissue transversal with no net axial force by means of microstructures on the needle surface has been reported in [6], [16], [19]. Similarly, inspired by insertion methods observed in mosquito proboscis, Aoyagi et al [20] indicated that substrate penetration with a microneedle comprising serrated stylets is possible without applying a net push force (see also [21] for a description of buckling prevention in mosquitos and wasps).…”
Section: The Wasp Ovipositor and Biologically Inspired Steerable Needlesmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, Oldfield et al [18] described a 6-mm diameter four-part needle prototype with reciprocally moving segments. Tissue transversal with no net axial force by means of microstructures on the needle surface has been reported in [6], [16], [19]. Similarly, inspired by insertion methods observed in mosquito proboscis, Aoyagi et al [20] indicated that substrate penetration with a microneedle comprising serrated stylets is possible without applying a net push force (see also [21] for a description of buckling prevention in mosquitos and wasps).…”
Section: The Wasp Ovipositor and Biologically Inspired Steerable Needlesmentioning
confidence: 95%
“…Several flexible steerable needles have been developed in an effort to overcome the path planning limitations encountered with rigid straight needles (e.g., [2], [4][5][6][7][8][9]). Some of these newly developed needles rely on concentric axial insertion of multiple pre-bent needle parts, whereas others rely on reaction forces from the tissue to control the steering curvature (for reviews see [10,11]).…”
Section: Percutaneous Needles: a Brief State-of-the-artmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, however, there have been efforts to use flexible needles to reach a target while avoiding 'no-go' areas. Apart from ours [3][4][5], these researches can be broadly classified into three main categories: needle steering methods based on the lateral motion of an external base and deformation of the soft tissue [6,7]; steering control of flexible needles with a fixed-shape bevel tip [8,9] and steering control using concentric tubes [10,11]. These methods have substantially advanced the state of the art, but there remain a number of outstanding research challenges which stand in the way of a widespread adoption of these technologies.…”
Section: Introductionmentioning
confidence: 93%
“…Catheters can place the micro-systems using external force (Frasson et al, 2007). Various swimming methods have been suggested using magnetic (Zhang et al, 2009;Yesin et al, 2006;Ishiyama et al, 2001), piezoelectric (Kosa et al, 2007, Watson et al, 2009) and electro active polymer (Guo et al, 2006) actuators.…”
Section: Introductionmentioning
confidence: 99%